2016
DOI: 10.3233/jad-150660
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Evaluating the Impact of Physical Exercise on Disease Progression in a Mouse Model of Alzheimer’s Disease

Abstract: Abstract. Evidence suggests that physical exercise can serve as a preventive strategy against Alzheimer's disease (AD). In contrast, much less is known about the impact of exercise when it is introduced after cognitive deficits are established. Using the TgCRND8 mouse model of amyloidosis, we compared the effects of exercise as an intervention strategy aimed at altering disease progression. Voluntary running for 1 month or 2 months was introduced in 3-month-old TgCRND8 mice, which exhibit amyloid-beta (A␤) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Behavioral deficits in the Tg mice are robust, given that significant differences persisted despite being housed in cages with running wheels. Previous research has shown that wheel-running exercise in AD mice led to improved performance in various behavioral tasks, including: Barnes Maze (Walker et al, 2015 ), Y-maze (Maliszewska-Cyna et al, 2016 ), and the MWM (Adlard et al, 2005 ). In addition, voluntary wheel running has also been shown to decrease plaque pathology (Adlard et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral deficits in the Tg mice are robust, given that significant differences persisted despite being housed in cages with running wheels. Previous research has shown that wheel-running exercise in AD mice led to improved performance in various behavioral tasks, including: Barnes Maze (Walker et al, 2015 ), Y-maze (Maliszewska-Cyna et al, 2016 ), and the MWM (Adlard et al, 2005 ). In addition, voluntary wheel running has also been shown to decrease plaque pathology (Adlard et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that increased physical activity or an active lifestyle beneficially affects human brain health (Scarmeas et al, 2009), and reduces the pathological plaque load and improves cognition in patients with AD (Maliszewska-Cyna et al, 2016). However, the mechanisms underlying the effect of physical activity on the reduction of plaque remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Running has also been shown to reduce microglia activation and cytokine levels in the hippocampus of aged mice, representing another mechanism by which exercise may protect the neurovascular unit and in turn, the brain from insult [ 6, 94, 95 ]. In models of advanced aging and Alzheimer’s disease (AD), exercise reduces soluble amyloid-beta (A β ) load and plaque formation, in part mediated by glymphatic clearance and proteolytic degradation [ 76, 94, 96–99 ]. Voluntary exercise has also been shown to delay white matter atrophy and protect cerebral vasculature in mouse models of AD, correlating with improved performance on spatial memory tasks [ 100–102 ].…”
Section: Introductionmentioning
confidence: 99%